Généralisation de l'éducation au développement durable et territorialisation des établissements scolaires - Stéphane Bonnet; Angela Barthes
Sustainable development policies encourage schools to contextualize themselves in their environments. We postulate that the generalization of Education for Sustainable Development (ESD) and the territorialization of schools are inextricably linked. After defining and criterifying the generalization of ESD and the territorialization of second degree institutions, we study fourteen them spread over three departments in the mountain countryside of southern France. The method consists of the analysis of school projects by extracting lexical occurrences relating to sustainable development policy and territorialization, coupled with interviews with school heads. We note a correlation between the territorialization index and the generalization index of ESD in deep rural areas. In each case, the pooling of resources with other institutions and the territorial involvement of the head of the institution are decisive.